EFFECT OF USING FERMENTATION PALM CORE PALM CARNEL CAKE AND CASSAVA WASTE IN FORMULATION FEED TO BROILER WHICH IS ADDING WITH EXTRACT Morinda Citrifolia FOR FEED CONSUMPTION,OF BODY WEIGHT GAIN, FEED CONVERSION AND FEED EFFICIENCY - Jondani, Debi (Jurnal Sains Peternakan, 2015)
The aim of this research was to know the effect of adding fermentation of cassava waste and palm carnel cake which is adding with extract Morinda Citrifolia  in formulation feed of broiler  to feed consumption ,body weight gain,  feed conversion, and efficiency  of feed using. Materials were used in this reserch are 96 broiler chickens  unsexed  which is produced by PT Japfa Comfeed Indonesia tbk. Methodology used in this reserch is experiment by using complete  random with 8 treatment, those are P0M0 (feed 100%), P1M0 (feed+10% fermentation ), P2M0 (feed+20% fermentation) P3M0 (feed +30% fermentation ) And by Morinda Citrifolia that is P0M1 (feed + Morinda Citrifolia) P1M1 (feed + morinda citifolianin +10% fermentation) P2M1 (feed + Morinda Cirtifolia +20% fermentation) P3M1 (feed + Morinda Citrifolia +30% fermentation) and each treatments are repeared 3 times. Each treatment consist of a chickens. The summary of tonglusion using fermentation of palm core bis, and cassava waste in formulation feed to chickens which is combined with extract Morinda Citifolianin does not give real effect to feed consumption, but give real effect for adding of the chickens weight feed converesion and efficiency in using feed of the chickens. There were no significant effect of using feed consumption, while very significant on body weight gain, feed conversion, and feed efficiency. It could be suggested to increase level fermented palm carnel cake and Morinda Cirtifolia extract in broilerKeywords: Fermentation, palm carnel cake, cassava waste, Morinda Citrifolia, and Broiler